Discrepancies in degree of conversion measurements by FTIR - Fabrício Mezzomo Collares; Fernando Freitas Portella; Vicente Castelo Branco Leitune; Susana Maria Werner Samuel (Sociedade Brasileira de Pesquisa Odontológica, 2014)
The purpose of this study was to evaluate the influence of the internal standard peak on the measured degree of conversion (DC) for methacrylate-based resins analyzed by Fourier-transform infrared spectroscopy (FTIR). The influence of different baseline measurement methods was also determined. Different blends were prepared, mixing BisGMA/BisEMA and BisGMA/TEGDMA at proportions of 0% to 100%, in weight. Camphoroquinone and ethyl-4-dimethylamino-benzoate were used to permit the light activation of blends. Degree of conversion was evaluated using FTIR equipped with an attenuated total reflectance (ATR) device. Samples were dispensed onto ATR crystal and light activated for 40 s. The DC was calculated by relating the height of the peak 1637 cm-1 to the intensity of different internal standard peaks (1715, 1608, or 1582 cm-1), measured using two different baseline methods, before and after polymerization. Data were compared by ANOVA at 5% significance. The relationship between DC and monomer ratio was obtained by regression analysis. Double-bond conversion ranged from 32.75% to 78.50% for BisGMA/BisEMA blends, and from 32.75% to 76.22% for BisGMA/TEGDMA blends. For the BisGMA/BisEMA blends, the DC showed a linear association with the composition of the comonomer blends, independent of the internal standard peak and baseline method used. In contrast, the trends in DC for BisGMA/TEGDMA blends were different for each method of measurement. The internal standard peaks and measurement baseline should be taken into account when using FTIR to calculate the DC of methacrylate-based resins, especially comonomer blends containing a high degree of monomers that lack aromatic rings.